Observation of apparent MOS regimes on Al/PECVD grown boron nitride/p-c-Si/Al MIS structure, investigated through admittance spectroscopy - Ozdemir, Orhan (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
PECVD grown boron nitride (BN) on crystalline silicon (c-Si) semiconductor was investigated by admittance measurement in the form of metal/insulator/semiconductor (MIS) structure. Apart from well-known regimes of traditional MOS structure, gradual bypassing of depletion layer was observed once ambient temperature (frequency) increased (decreased). Such an anomalous behavior was interpreted through modulations of charges located within BN film and/or at the interfacial layer of BN film/c-Si junction in terms of weighted average concept. (C) 2008 International Association for Hydrogen Energy. Published by Elsevier Ltd. All rights reserved.
Keywords: Boron nitride; Apparent MOS regimes; Surface band bending; Chemistry; Electrochemistry; Energy & Fuels